Pamidronate and zoledronate effects in the increment of bone mineral density and histomorphometry in rats - Cruz Júnior,Antônio Fiel (2011)
PURPOSE: To compare increment of bone mineral density (BMD) with pamidronate, zoledronate and the isolated effect of proteinous diet in undernourished oophorectomized and non-oophorectomized female rats, besides validating BMD's indexes. METHODS: 60 young female Lewis rats were divided into five experimental groups and a control group, oophorectomized and non-oophorectomized. The administration of drugs were submitted to proteinous and aproteinous diets. The variables analyzed were weight, bone densitometry, histomorphometry and biochemical evolution. RESULTS: In weight evaluation, the first interval showed a statistically meaningful increase in oophorectomized sample. In densitometry evaluation, the first interval showed statistically meaningful decrease in four medicated groups and third showed a statistically meaningful increase in 2 non-oophorectomized groups. In laboratory evaluation, there were an increase of total proteins and globulin, decrease of alkaline phosphatase, phosphorus and calcium (except for the oophorectomized) in four medicated groups and increase of phosphorus and calcium in 2 not medicated groups. In histomorphometric evaluation, the oophorectomized groups had smaller increment of BMD. CONCLUSIONS: The pamidronate and zoledronate have shown effectives in the increment of BMD. The proteinous diet itself possesses therapeutic effect in BMD though not significant compared with medicated animals. The results of histomorphometry allow validating BMD's indexes in this experimental model.